Fed Cattle Quality - Mintert, James R.; Brazle, Frank K.; Schroeder, Ted C.; Jones, Rodney; Albright, Martin L. (My University, 1993)
This publication describes a study designed to investigate fed cattle pricing in southwestern Kansas.
MF1071 _1993_07
Keywords: MF1071; Livestock; Economics; MF